English Teacher’s Challenges in Assesing English Proficiency of Student with Autism Spectrum Disorder in Inclusive Classroom - Dea Nita Aulia; Farida Repelita Waty Br. Kembaren (Universitas Cokroaminoto Palopo, 2026)
This study explores the challenges faced by an English teacher in assessing the English proficiency of students with Autism Spectrum Disorder (ASD) in an inclusive classroom and the adaptive assessment practices used to address these challenges. A qualitative single-case study was conducted at one inclusive junior high school in Medan, Indonesia, involving one English teacher. Data were collected through classroom observations, semi-structured interviews, and document analysis and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that the teacher encountered difficulties in assessing productive skills due to students’ social-pragmatic communication barriers, while receptive skills were affected by slower cognitive processing, limited instructional time, and emotional regulation challenges. To address these challenges, the teacher implemented adaptive assessment practices, including simplified instructions, visual supports, extended time, flexible oral assessment, collaboration with a shadow teacher, and portfolio-based evaluation. These practices appeared to support more equitable and meaningful assessment while maintaining academic expectations within the context of this case study. Because this study involved only one teacher in one inclusive school, the findings should be interpreted as context-specific and may not be generalizable to other educational settings.